PENDIDIKAN ISLAM PLURALIS DAN MULTIKULTURAL - Muhammad Yahya (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
Pluralism denotes an acceptance of plurality in the community. Plurality in terms of diversity means that human from different background live together under no circumstances. There are different reasons why diversity occurs. It may because of the way of thinking and the attitude to an object which is due to different life styles. The plural and multicultural concept in Islamic Education is equivalent to the concept of ‘silaturrahim’, which means a mutual respect and love among the creatures regardless of ethnic and religious background. Islamic Education does not only concern the hereafter, but the worldly life as well through integrated education.